THE EFFECTIVENESS OF SELCOPINTIDE-CONTAINING TOOTHPASTE AMONG PEOPLE WITH DENTIN HYPERSENSITIVITY IN THANH XUAN WARD, HANOI CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of a toothpaste containing Selcopintide in reducing dentin hypersensitivity among residents with dentin hypersensitivity in Thanh Xuan Ward, Hanoi, in 2025. Methods: This was a clinical trial evaluating three types of toothpaste: Selcopintide, Potassium Nitrate, and Fluoride. A total of 156 participants aged 18–65 years were followed up and included in the analysis.Results: After the intervention, VAS and Schiff scores gradually decreased over time in all three groups under both air-blast and ice-water stimuli. The Selcopintide group showed greater improvement than the two control groups, reaching the highest effectiveness at weeks 3–4 and maintaining good effectiveness until week 5 after switching to Fluoride toothpaste. The reductions in VAS/Schiff scores were 41.00%/32.44% under air-blast stimulation and 48.29%/43.42% under ice-water stimulation. The Potassium Nitrate group showed high effectiveness initially, but its effect decreased after switching to Fluoride toothpaste, while the Fluoride group showed a lower level of improvement. The improvement was statistically significant at most time points, with p < 0.05. Conclusion: Toothpaste containing Selcopintide demonstrated a clear effect in reducing dentin hypersensitivity, maintained stable effectiveness after switching back to Fluoride toothpaste, and shows potential for application in community oral healthcare.
Keywords: Dentin hypersensitivity, Selcopintide, toothpaste, intervention.